Scientists’ Assessments of Research on Lactic Acid Bacterial Bacteriocins 1990–2010 - Martinenghi, Laura D.; Leisner, Jørgen J. (Frontiers in Microbiology, 2022)
The antimicrobial activity of bacteriocins from lactic acid bacteria has constituted a very active research field within the last 35 years. Here, we report the results of a questionnaire survey with assessments of progress within this field during the two decades of the 1990s and the 2000s by 48 scientists active at that time. The scientists had research positions at the time ranging from the levels of Master’s and Ph.D. students to principal investigators in 19 North American, European, Oceanian, and Asian countries. This time period was evaluated by the respondents to have resulted in valuable progress regarding the basic science of bacteriocins, whereas this was not achieved to the same degree with regards to their applications. For the most important area of application, food biopreservation, there were some success stories, but overall the objectives had not been entirely met due to a number of issues, such as limited target spectrum, target resistance, poor yield as well as economic and regulatory challenges. Other applications of bacteriocins such as enhancers of the effects of probiotics or serving as antimicrobials in human clinical or veterinary microbiology, were not evaluated as having been implemented successfully to any large extent at the time. However, developments in genomic and chemical methodologies illustrate, together with an interest in combining bacteriocins with other antimicrobials, the current progress of the field regarding potential applications in human clinical microbiology and food biopreservation. In conclusion, this study illuminates parameters of importance not only for R&D of bacteriocins, but also for the broader field of antimicrobial research.